G577(P) Improving recording of postnatal ward neonatal observations. (27th April 2015) - Parkinson, K; Lim, Y; Demetriou, A; Ziprin, J
Abstract : Context: This audit was carried out on two postnatal wards at different sites within the same trust. Problem: Whilst working on the postnatal wards we observed that the observations that babies required (e.g. after meconium delivery) weren't being carried out according to the frequency specified in the guidelines. Therefore causing a negative impact on patients due to the potential for missing a deterioration if observations were not carried out appropriately. Assessment of problem and analysis of its causes: We found on average 41% of the recommended frequency of observations were carried out on site 1 and 52% on site 2. More than 50% of the recommended observations were not done in the following categories; maternal GBS, phototherapy and hypoglycaemia in site 1 and in site 2; hypoglycaemia, and 33–35+6/40 gestation. It was felt a possible reason why such a low percentage of observations were completed was due to lack of awareness of the frequency specified in the guidelines. Additionally at site 1 there is no set place to record observations whereas at site 2 separate charts are used. This may explain the higher percentage of recorded observations at site 2. Following these hypotheses we developed a structured observation chart. Intervention: The chart we developed is contained on an A4 sheet. At the top there is a table with all the reasons for a baby requiring observations with the corresponding frequency of observation required. At the bottom there is a chart where the observations can be recorded. This incorporates a neonatal early warning system (NEWS) which can help to flag up early deterioration in patients (see inserted image). Study design: This audit was a prospective study. Over two weeks all babies on the two postnatal wards that required observations were analysed. The outcomes recorded were; the reason for the baby requiring observations and the frequency of observations carried out. Strategy for change: Currently the new observation chart is being approved by the care management group. After this has been done we will need to train the midwifes to use the chart, calculate the NEWS score and how to act on it. This will take around 6 months. Measurement of improvement: Once the chart has been implemented we will re-audit using the initial audit design. We will then compare the results to ascertain if the new chart has resulted in improvement in the frequency of observations. Effects of changes: The new observation chart has not yet been implemented into practice, however once it is in use it will be clearer how often observations need to be done and deterioration of a patient will be flagged up earlier therefore improving patient safety. A potential problem will be training the staff across sites to use the chart effectively. Lessons learnt: Awareness of the guidelines is key in ensuring their implemented. When it is not clear how often observations need to be done the frequency is well below the expected standard. However by implementing a chart that makes the frequency of observations clear and by combining a recording chart with NEWS it is hoped that recording of observation will dramatically increase and therefore improve patient safety. Message for others: As junior doctors it is key that when we spot something on the wards that affects patient safety we investigate its extent and root cause. We can then implement changes to improve patient safety. By using an observation chart which specifies the frequency of observation the number then missed will reduce, therefore any deterioration in a baby's observations will be spotted earlier. Additionally by using a NEWS the midwives will have a guide on how to act when a baby has abnormal observations. This again will help to identify unwell babies earlier.